PELATIHAN PENGEMBANGAN MEDIA INFORMASI BERBASIS CANVA UNTUK MENINGKATKAN KREATIVITAS REMAJA KARANG TARUNA DALAM MENINGKATKAN EKONOMI KREATIF DESA TROPODO KRIAN SIDOARJO - Budi Purwantiningsih; Nayla Najma Arifin; Novita Andriana; Ainur Rosyidah; Elok Imroatul Azizah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
Information media is widely used in daily activities, including social media, marketplaces, promotions, banners, flyers, pamphlets, and brochures. However, to effectively engage the community, the chosen media must feature well-designed, unique, and attractive visuals that motivate action. Tropodo Village has an official website but lacks the human resources to utilize it for promoting local products through the development of Micro, Small, and Medium Enterprises (MSMEs) and the